Case Report: Angiomatoid fibrous histiocytoma in the hand: a rare clinical presentation and diagnostic challenge - Ichikawa, Jiro; Kawasaki, Tomonori; Imada, Hiroki; Wako, Masanori; Fujimaki, Taro; Tatsuno, Rikito; Jubashi, Takahiro; Haro, Hirotaka (Frontiers in Oncology, 2023)
Angiomatoid fibrous histiocytoma (AFH) is a rare tumor of mesenchymal origin occurring in young adults. Based on its clinical course, it is said to have an intermediate potential. We present a case of a 59-year-old woman with AFH in the hand that was difficult to diagnose. A benign soft tissue tumor was suspected on magnetic resonance imaging, and its size and open biopsy suggested nodular fasciitis or inflammatory myofibroblastic tumor. A diagnosis of AFH was eventually made based on the analysis of the resected specimens. The characteristic findings of histopathology and immunohistochemistry in this case were relatively poor, so fluorescence in situ hybridization contributed to making the correct diagnosis. Considering its prognosis, careful follow-up was decided upon without additional surgery. Our case is a challenging one because of its atypical presentation and inconclusive imaging and histopathological findings.